GAME-THEORETIC FORMALIZATION OF LABOR RELATIONS IN THE AGRI-FOOD SECTOR OF ECONOMY - Волошин, Р. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article is considered with theoretical and methodological principles of the application of game theory in the study of labor relations in the agro-food sector of the econom; the main trends of the labor market in the sector are outlined; the expediency and validity of the application of game theory for assessing and modeling the behavior of participants in labor relations are analyzed; the main categories of game theory from the point of view of labor relations are identified; the main types of player behavior strategies are defined and characterized; the expediency of cooperation between them are emphasized; the formalization of the players' behavior strategies in the form of a matrix has been done.